Psychology of impulsivity : new research - Olmstead, Mary C. (Psychology of emotions, motivations, and actions series., 2014)
Impulsivity is a primary feature of many psychiatric conditions and often leads to maladaptive behaviors in nonclinical populations. This predisposition to rapid, unplanned actions and a disregard for future, negative consequences leads to seemingly irrational and self-defeating behaviours including substance abuse, pathological gambling, binge eating, and self-harm. Even in young children, impulsivity can have detrimental and long-lasting effects: deficits in impulse control predict poor academic performance and are correlated with behavioural, social, and emotional problems. This book provid.